Assessment of the feed additive consisting of calcium D‐pantothenate for all animal species for the renewal of its authorisation (BASF SE) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of calcium D‐pantothenate for the renewal of its authorisation as a nutritional feed additive for all animal species. The additive calcium D‐pantothenate is already authorised for use in all animal species (3a841). The applicant provided evidence that the additive currently in the market complies with the existing conditions of the authorisation and that the production process has not been modified. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive remains safe for all animal species, consumers and the environment. Calcium D‐pantothenate is not irritant to skin and eyes and is not a skin sensitiser. The present application for renewal of the authorisation does not include any modification proposal that would have an impact on the efficacy of the additive, and therefore, there is no need for re‐assessing the efficacy.